DOMINANT SPECIES OF THE GENUS PROTOPERIDINIUM BERGH (PERIDINIALES: PROTOPERIDINIACEAE) IN THE BLACK SEA - Krakhmalnyi, Aleksandr F.; Krakhmalnyi, Maxim A.; Terenko, Galyna V.; Goncharenko, Igor V. (Zootaxa, 2023)
To date, 59 species (61 including infraspecific taxa) of the heterotrophic genus Protoperidinium have been found in the Black Sea. With rare exceptions, the records of most species were not confirmed by either line drawings or microphotographs, and lacked indications of important diagnostic traits. To partially correct these deficiencies, we conducted morphological examinations of the dominant Protoperidinium species in the Black Sea. The study provides original descriptions, line drawings, and microphotographs of 22 species of Protoperidinium with their global distribution maps. Protoperidinium quadrioblongum is reported from the Black Sea for the first time.